Readily Accessible Fluorescent Probes for Sensitive Biological Imaging of Hydrogen Peroxide - Daniel, Kevin B.; Agrawal, Arpita; Manchester, Marianne; Cohen, Seth M. (Chembiochem : a European journal of chemical biology, 2013)
Hydrogen peroxide is a major component of oxygen metabolism in biological systems that, when present in high concentrations, can lead to oxidative stress in cells. Noninvasive molecular imaging of H2O2 using fluorogenic systems represents an effective way to detect and measure the accumulation of this metabolite. Herein, we detail the development of robust H2O2‐sensitive fluorescent probes using a boronic ester trigger appended to the fluorophore through a benzyl ether linkage. A major advantage of the probes presented here is their synthetic accessibility, with only one step needed to generate the probes on the gram scale. The sensitivity of the probes was evaluated in simulated physiological conditions, showing micromolar sensitivity to H2O2. The probes were tested in biological model systems, demonstrating effective imaging of unstimulated, endogenous H2O2 levels in RAW 264.7 cells and murine brain tissue. Turning on the light: The preparation, reactivity, and imaging properties of a new class of fluorescence‐based molecular probes is reported for the detection of endogenous hydrogen peroxide (H2O2). These probes are easy to synthesize, which should make them an accessible tool for probing the chemical biology of reactive oxygen species.